Project Management for Healthcare Informatics - Houston, Susan; Bove, Lisa Anne.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2007)
Project Management for Healthcare Informatics provides an explanation of the project management process tailored for nurses through its use of real clinical examples. In the first chapters, the project management process will be described in detail along with its relationship to the phases of the project life cycle. The tools available to successfully complete each phase of the project management process and move along the project life cycle will be included. The rest of the book will be devoted to discussion on how to apply these principles in the day-to-day work of the nurse—whether manager, staff nurse, educator, researcher, or informatician. Case studies and project examples will comprise the majority of material in these chapters. Susan M. Houston, MBA, RN, BC, PMP, is a project manager in the Department of Clinical Research Informatics at the National Institutes of Health in Bethesda, Maryland. Lisa Anne Bove, MSN, RN, BC, is a project management consultant with Accenture in Philadelphia, Pennsylvania.
Project Management Process -- Initiation Phase -- Planning Phase -- Execution Phase -- Control Phase -- Closing Phase -- Applying the Project Management Process in Healthcare Informatics -- Applying the Project Management Process in Healthcare Management -- Summary.
Keywords: Health informatics; Nursing; Nursing administration; Nursing—Research.; Health Informatics; Nursing; Nursing Management; Nursing Research